In chronic exile: A critique of South Africa's legal regime for refugees in protracted refugee situations - Khan, Fatima (Department of Public Law, 2020)
The major thrust of refugee protection worldwide is directed towards providing assistance to refugees in emergency situations. In South Africa, a large number of refugees have moved beyond this initial emergency phase such that the extended nature of their refugee status has left them in a state of continuous vulnerability. Their prolonged exile has led to violations of various rights recognised by international law and South Africa’s own constitutional and refugee law. Faced with restricted access to rights, refugees in South Africa live in poverty, are frustrated, and do not realise their full potential, to say nothing about the overt and brutal attacks they constantly face as victims of xenophobia. Their continued status as refugees deprives them of opportunities and subjects them to constant fear of harassment and exploitation. Even though neither the UNHCR nor the South African government has classified refugees living in South Africa as being in a protracted situation, many refugees have been in South Africa for five years or longer, with no durable solution in sight. This thesis highlights the plight of refugees in protracted refugee situation in South Africa and recommends suitable solutions to the problems this situation raises.